2021
DOI: 10.1590/0103-8478cr20200423
|View full text |Cite
|
Sign up to set email alerts
|

Nisin and ε-poly-L-lysine as natural antimicrobials towards spoilage-associated Lactobacillus plantarum

Abstract: Sausages are highly susceptible to microbial spoilage. Lactic acid bacteria (LAB) is the main group of spoilage bacteria in vacuum packed cooked sausages. To control microbial growth natural antimicrobials have been used as food preservatives. The aim of this study was to identify strains of lactic acid bacteria isolated from spoiled commercial Calabresa sausages and use them in an in vitro challenge with the natural antimicrobials, nisin (NI) and ε-poly-L-lysine (ε-PL). Mass spectrometry identification of LAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…is result was consistent with the findings reported by Bortolotto et al [29] and Geornaras et al [30]. It was also observed that lower temperature and higher concentrations enhanced inhibition efficacy of nisin or ε-PL on the growth of L. lactis synergistically.…”
Section: Growth Of L Lactis and Background Microorganisms In Fvfbsupporting
confidence: 93%
“…is result was consistent with the findings reported by Bortolotto et al [29] and Geornaras et al [30]. It was also observed that lower temperature and higher concentrations enhanced inhibition efficacy of nisin or ε-PL on the growth of L. lactis synergistically.…”
Section: Growth Of L Lactis and Background Microorganisms In Fvfbsupporting
confidence: 93%
“…In addition, the combination of ε-PL with other food additives can further improve the antimicrobial effect ( Sun et al, 2018 ). For example, minimal inhibitory concentration of ε-PL and nisin (another natural food preservative) towards spoilage Lactobacillus plantarum were and 75 and 0.468 mg/L, respectively, while the combined use of ε-PL and nisin at much smaller concentrations (9.375 and 0.05 mg/L) can completely inhibit the growth of spoilage L. plantarum ( Bortolotto et al, 2021 ). In another research, the combined use of ε-PL (200 mg/L) and chitooligosaccharide (400 mg/L) also showed much stronger antifungal activity against B. cinerea than the use of ε-PL (200 mg/L) or chitooligosaccharide (400 mg/L) alone ( Sun et al, 2018 ).…”
Section: Recent Advances In Applications Of ε-Plmentioning
confidence: 99%